Biocompatibility of dental resin composites - Rahmi Khairani AULIA (Journal of Syiah Kuala Dentistry Society, 2022)
Dental resin composites have become the first choice among the filling materials due to their aestheticpotential to suit a variety of therapeutic indications and can conserve the tooth structure. However, there areconcerns that this material may be toxic because of the possibility of releasing components after restoration.Bisphenol-A (BPA) is a primary material for dental resins that is a precursor for BisGMA as a natural resin, anddegradation of dental resins can leach BPA to the oral cavity. Despite the possibility of a leachable substance, manystudies concluded that the release of BPA from dental resin composites might not be absorbed systemically. Theyleached less than the toxic level that may cause adverse effects.KEYWORDS: BisGMA, BPA, resin composites,